An Advanced BIST Architecture with Low Power LBIST and BDS Oriented March Algorithm for Intra Word Coupling Faults (International Journal of Engineering and Computer Science, 2017)
Today’s System-on-Chips (SoCs) design and test confront several problems, especially power dissipation. Generally, power dissipation of a system in test mode is more than in normal mode. This is because a significant correlation exists between consecutive vectors applied during the circuit’s normal mode of operation, whereas this may not be necessarily true for applied test vectors in the test mode. Reduced correlation between the consecutive test vectors increases the switching activity and eventually the power dissipation in the circuit. The second reason of increasing the power dissipation during test is because the test engineers may test cores in parallel to reduce the test application time. This extra power (average or peak) can cause problems such as instantaneous power surge that causes circuit damage, difficulty in performance verification and decreased overall product yield and cost. Low power test application has become important in today’s VLSI design and test.